Causas de óbito em animais de tráfico e resgate no estado da Paraíba - Soares, Karoline Lacerda (2022)
Unbalanced human and animal interaction, as well as illegal commercialization of wild animals, contribute to the loss of species. In addition, close contact can mean the transmission of zoonoses. In this context, the objective is to describe the main causes of death in animals apprehended from trafficking and rescued by the Center for Triage of Wild Animals of Paraíba (CETAS-PB). The dissertation was divided into three chapters. The first chapter addresses the causes of death of wild animals sent by the Center for Triage of Wild Animals of Paraíba for necropsy at the Veterinary Pathology Laboratory of the Veterinary Hospital of the Federal University of Paraíba. A total of 101 (76.5%) birds, 19 (14.4%) mammals and 12 (9.1%) reptiles were necropsied. All reptiles and mammals were rescued, whereas in the group of birds, 54 (53.5%) were seized by the environmental police, 40 (39.6%) were rescued and 7 (6.9%) were voluntarily delivered. Diagnosed diseases were divided based on etiology into traumatic with 39 (29.5%) cases, infectious caused by bacteria with 4 (3.0%) cases, fungus with 1 (0.8%) case, parasitic with 1 ( 0.8%) case and neoplastic with 2 (1.5%) cases. In the remaining 85 (64.4%) cases the diagnosis was not possible, of which one (0.75%) was inconclusive, 17 (12.87%) without alteration and 67 (50.75%) were autolyzed. Knowledge about the diseases that affect these animals is important for preventing the transmission of zoonoses in addition to supporting measures for the conservation of the species. The second chapter describes the macroscopic and microscopic findings of a metastatic hepatocellular carcinoma in a blue parrot (Amazona aestiva). At the opening of the cavity, there was a mass restricted to the right hepatic lobe and, on the dorsal surface of the left lung lobe, a rounded, well-delimited nodule. Microscopically, in the liver, partial replacement of the parenchyma was observed by neoplastic proliferation of cuboidal epithelial cells, cells of the same appearance were observed in the pulmonary nodule and in the kidney, multiple neoplastic emboli were visualized in small capillaries in the cortical region This is the first report of this tumor that occurred in this species in Brazil and should be included as a differential between neoplastic and non-neoplastic hepatic disorders with nonspecific symptoms. The third chapter describes the anatomopathological, microbiological and molecular findings of an outbreak of esophagitis and ingluvitis caused by Salmonella Typhimurium in adult male Sporophila passerines from seizures. At necropsy, yellowish plaques were observed in the esophagus and ingluvium. In the histopathological evaluation, multifocal to coalescing ulcers were observed, with extensive necrosis, presence of heterophils and bacterial aggregates. In the microbiological isolation, the bacteria Salmonella spp. then confirmed by MALDI-TOF. Samples were collected from the enclosures and cages where the animals were in quarantine and it was possible to isolate the same agent. The strains showed resistance to Penicillins, Sulfonamides, Aminoglycosides, Monobactams, Tetracyclines, 1st and 3rd generation Cephaslosporins. The Typhimurium serotype was identified in two birds. The diagnosis of the disease, as well as the isolation of the agent involved, allows to know the harmful potential of this disease in passerines and allows the development of measures for the prevention of zoonoses, since this serovar is an important cause of diseases in humans and domestic animals.